The use of social networks in institutional communication at university: a prospective pattern for enhancing the sense of belonging among students - Galioto, Marina; Pedone, Francesca; Vantarakis, Apostolos; Tavares, Paula; Bianco, Antonino (Frontiers in Communication, 2025)
Considering that universities follow trends closely in worldwide digital innovation, this community case presents how organizational communication examined and implemented new ways of connecting people in digital environments. A new official Meta profile at the university that was created as part of an innovative communication plan at the department level was utilized for this purpose. The results of a 12-month trial revealed that social connections between people fit with digital connections. In this experimental design of organizational communication, the following two paths were followed: planning social experiences to stimulate student engagement and promoting these initiatives through social networks (i.e., Facebook and Instagram). To connect the students and instill the feeling of belonging to their institution, a specific design was also implemented to restructure the traditional approach to social media dialogue, considering that students, teachers, and academic staff are all part of the same community; instead of a conventional style based on informational language, a more conversational style was used, with the audience being involved as much as possible through questions, surveys, mentions, and collaborative posts to foster their sense of inclusion. As we managed the organization of an educational visit abroad for our students, they were invited to share their feelings, perceptions, and comments via social media with photographs and videos of this experience. This methodology, which focused on social activities linked to digital connections, proved to be a great opportunity for building a type of combined institutional storytelling, embedded in a natural sense of community. Moreover, this joint vision of the academic community, fulfilled by real-life events and not only stories displayed through social networks, is fundamental to creating a brand identity that fosters a sense of belonging.